Text-messaging to reduce missed appointment in a youth clinic: a randomised controlled trial. Issue 10 (12th June 2013) - Narring, Françoise; Junod Perron, Noëlle; Dominicé Dao, Melissa; Camparini Righini, Nadia; Humair, Jean-Paul; Broers, Barbara; Gaspoz, Jean-Michel; Haller, Dagmar M
Abstract : Background: To assess the effectiveness of text-messages in reducing the proportion of non-attendance in a youth clinic of a University Hospital. Methods: Patients who registered for an appointment and provided a mobile phone number were randomly selected to receive or not a text-message reminder before the planned appointment. A 10% reduction in the proportion of missed appointments was considered clinically and economically useful and the study was powered accordingly. Results: The proportion of missed appointments was 16.4% (95% CI 13.1% to 19.8%) in the text-message group (N 462) and 20.0% (95% CI 16.6% to 23.4%) in the control group (N 529), showing no significant effect of the intervention (p=0.346). Conclusions: In our primary care youth clinic, text-message reminders are not effective in reducing the proportion of missed appointments. This may in part be due to the fact that most patients are referred by a professional or by their parents and do not initiate appointments themselves.